Concentrations of arsenic and vanadium in environmental and biological samples collected in the neighborhood of petrochemical industries: A review of the scientific literature - González, Neus; Esplugas, Roser; Marquès, Montse; Domingo, José L. (The Science of the total environment, 2021)
Petrochemical facilities, including oil refineries, are emission sources of a wide range of environmental pollutants such as trace elements, volatile organic compounds, and polycyclic aromatic hydrocarbons, among others. Populations living near this kind of facilities may be potentially exposed to contaminants, which are, in turn, associated with a wide range of adverse effects. In our laboratory, we have shown that the environmental concentrations of trace elements near the petrochemical complex of Tarragona County (Spain), which is among the largest complexes in the European Union, should not be a relevant pollution source for these elements, with the exception of arsenic (As) and vanadium (V). Moreover, the International Agency for Research on Cancer (IARC) classified As and V as Group 1 and Group 2B, respectively. Based on it, the present paper was aimed at reviewing the available scientific information on the occurrence of As and V in the vicinity of petrochemical complexes worldwide, considering environmental matrices (air, dust, sediments, soil, and water), as well as biological samples (blood, hair, and urine). In general, levels of As and V in environmental matrices showed higher fluctuation throughout the world and was highly dependent on the samples zone while levels of both elements in urinary samples from subjects living near a petrochemical area were higher than those of population living further. [Display omitted] •As and V levels in samples collected near petrochemical areas are reviewed.•Both As and V levels show notable fluctuations throughout the world.•Higher urinary levels of As and V are found in subjects living in these areas.